Carbon Lorenz Curves - Loek F. M. Groot (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2008)
The purpose of this paper is twofold. First, it exhibits that standard tools in the measurement of income inequality, such as the Lorenz curve and the Gini-index, can successfully be applied to the issues of inequality measurement of carbon emissions and the equity of abatement policies across countries. These tools allow policy-makers and the general public to grasp at a single glance the impact of conventional distribution rules such as equal caps or grandfathering, or more sophisticated ones, on the distribution of greenhouse gas emissions. Second, using the Samuelson rule for the optimal provision of a public good, the Pareto-optimal distribution of carbon emissions is compared with the distribution that follows if countries follow Nash-Cournot abatement strategies. It is shown that the Paretooptimal distribution under the Samuelson rule can be approximated by the equal cap division, represented by the diagonal in the Lorenz curve diagram.
Keywords: 330; carbon emission; climate change; Gini; global warming; Lorenz curve; Samuelson rule